First Spiritual Exercises and the Rise of Mental Wellbeing and OCB Among Credit Union Activists - Sumarwan, Antonius; Anggoro, Andreas Dion; Kristiyanto, Nikolas; Setiawan, Yohanes Ignasius (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates the effects of the First Spiritual Exercises (FSE) on mental well-being and Organizational Citizenship Behavior (OCB) among credit union activists. Contributing to the growing intersection of spirituality and organizational psychology, the study offers empirical evidence on how structured spiritual practices shape workplace behavior. A quasi-experimental design was applied to 53 activists, with the intervention group drawn from Credit Union Kridha Rahardja and the control group from Credit Union Kasih Sejahtera. Pre- and post-test analyses revealed significant improvements in mental well-being and OCB following participation in the FSE. Furthermore, mental well-being was found to have a statistically significant influence on OCB scores. These findings affirm that spiritual exercises may serve not merely as private devotion but as strategic levers for fostering psychological resilience and pro-social behavior in organizations. Managers may consider integrating reflective spiritual practices as part of employee development initiatives to promote healthier, more engaged work cultures.